执行指南《禁止生物武器公约》 - United Nations Office for Disarmament Affairs (United Nations, 2023)
The Guide to Implementing the Biological Weapons Convention has been developed by the United Nations Office for Disarmament Affairs (UNODA), with the support of the European Union and Norway and the contributions of a wide range of BWC experts, to assist States Parties in their efforts to implement the Convention at the national level. The Guide is primarily intended to provide an overview of the national implementation process and obligations stemming from the BWC. Its primary audience is States Parties initiating or already engaged in the BWC implementation process or States Parties interested in assessing their implementing framework. The Guide outlines the types of legislative, regulatory and other measures that States Parties may consider developing and adopting in order to effectively implement the BWC.